2014
DOI: 10.1002/jrs.4522
|View full text |Cite
|
Sign up to set email alerts
|

An acoustically enhanced gold film Raman sensor on a lithium niobate substrate

Abstract: The surface enhanced Raman scattering effect has shown immense potential for detecting trace amounts of explosive vapor molecules. To date, efforts to produce a commercially available, reliable SERS sensor have been impeded by an inability to separate the electromagnetic enhancement produced by the metallic nanostructure from other signal enhancing effects. Here, we show a new Raman sensor that uses surface acoustic waves (SAWs) to produce controllable surface structures on gold films deposited on LiNbO3 subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…describe a new Raman sensor that uses surface acoustic waves (SAWs) to produce controllable surface structures on gold films deposited on LiNbO 3 substrates that modulate the Raman signal of a target compound (in this case thiophenol) adsorbed on the films. The physi‐adsorbed molecules can be removed from the sensor without physical cleaning or damage, making it possible to reuse it for real‐time Raman detection . Leordean and corwokers reported multiscale electromagnetic SERS enhancement on self‐assembled micropatterned gold nanoparticle films, and found that the multiplicative enhancement effect is obtained by combining surface plasmon near‐field enhancement because of nanoscale features with far‐field photonic coupling by periodic microscale features .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…describe a new Raman sensor that uses surface acoustic waves (SAWs) to produce controllable surface structures on gold films deposited on LiNbO 3 substrates that modulate the Raman signal of a target compound (in this case thiophenol) adsorbed on the films. The physi‐adsorbed molecules can be removed from the sensor without physical cleaning or damage, making it possible to reuse it for real‐time Raman detection . Leordean and corwokers reported multiscale electromagnetic SERS enhancement on self‐assembled micropatterned gold nanoparticle films, and found that the multiplicative enhancement effect is obtained by combining surface plasmon near‐field enhancement because of nanoscale features with far‐field photonic coupling by periodic microscale features .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%